Seria wydawnicza „Książnica Tłumaczeń Łacińskich” - Kuć, Bogusława (Acta Universitatis Lodziensis. Folia Librorum, 2010)
During the period of twenty years between the wars in Poland there was a need for books in Latin, especially school books such as student books, obligatory readings and so called cribs. These books were published by many companies operating in different parts of Poland and they were usually grouped in publishing series : one of these series was “Książnica Tłumaczeń Łacińskich” published in Łódź by a family company of the Mittlers between 1928 and 1932. 44 volumes published as a part of this series contained translations and preparatory materials for Latin texts which belonged to the list of obligatory reading and were adjusted to grammar-translation method which was widely used at that time.